Communication Patterns in Improving Development Services in the Department of Public Works and Spatial Planning of the City of Tarakan - Sofia Risna Anwar; Dani Fadillah (Universitas Muhammdiyah Yogyakarta, 2024)
Public service is a service activity that cannot be separated from a person's daily activities. Public services themselves have been regulated in Law Number 32 of 2009 concerning Protection and the Environment which guarantees environmental welfare, so that this aspect is included in the development design strategy to achieve the main goal of sustainable development carried out by the government in order to protect the survival of future generations. This research aims to conduct a study regarding the communication patterns carried out by the Tarakan City PUPR Service in providing services to the community. The method used is literature study and uses a qualitative descriptive approach to examine the problem in more depth. The results of this research show that the Tarakan City PUPR Service has fulfilled 10 service indicators and has good service quality and in accordance with established standards.